Comparative analysis of oral health and treatment necessities in hemophilia individuals of Davangere population — A case control study - Varsha Kanjani; Rajeshwari G Annigeri; Suresh Hanagavadi; M R Manjunath (Journal of Family Medicine and Primary Care, 2020)
Background: The integrated approach towards the oral care of individuals with special needs requires proper motivation and prophylactic guidance by primary health care professionals, including musculoskeletal support to psychological therapy. In developing countries like India, oral care is not of primary importance as oral hygiene practices are less performed by compromised individuals suffering from hemophilia. Here, primary health care professionals play a significant role. The present study was commenced to evaluate oral health and treatment necessities in hemophilic individuals of Davangere population, Karnataka. Objective: The present study was conducted to assess and compare the oral hygiene, dentition status, and treatment needs of individuals with hemophilia. Methods: Simplified Oral Hygiene Index (OHI-S), decayed, missed, filled tooth (DMFT) indices and treatment needs in 50 hemophiliac patients registered at Karnataka hemophilia society were evaluated along with an Oral health-related quality of life (OHR-QoL) questionnaire. They were matched with healthy controls of the same age and gender. The data was analyzed using t test and Chi square test. Results: The oral hygiene was fair in both hemophilic and healthy individuals with a mean value of 1.82 ± 0.79 and 1.83 ± 0.73, respectively. All the parameters such as OHIS, DMFT indices, and teatment needs were not statistically significant. The spontaneous oral bleeding was the only significant factor in OHR-Qol questionnaire. Conclusion: The present study concluded that oral hygiene, dental caries prevalence, and treatment needs were similar in both hemophiliac and control groups. With proper guidance, motivation, and preventive care by primary health care professionals, it was relatively easy for individuals with congenital blood disorder (CBD) to maintain oral health-related quality of life in Davangere population, Karnataka.